Effect of high-frequency phase shift on metal transfer and weld formation in aluminum alloy double-wire DP-GMAW. (March 2022) - Wu, Kaiyuan; Zeng, Yucai; Zhang, Mingjin; Hong, Xiaobin; Xie, Peimin
Abstract: This paper presents a double-wire gas metal arc welding (GMAW) system for investigating the effects of high-frequency phase shift of the double pulse on metal transfer and bead formation. First, a theoretical analysis of the double-wire metal transfer process was carried out and a mathematical model of droplet impact was established. The metal transfer processes of different phase shifts were then photographed using a high-speed camera, the droplet velocity and impact on the weld pool at different phase shifts were calculated, and geometries of the weld beads were analyzed. Penetration of the longitudinal section fluctuated due to the modulated double pulse and the penetration depth increased with increasing phase shift; however, the weld reinforcement was irregular. The weld width increased with decreasing phase shift due to the temperature gradient. Moreover, since a reduction in double arc interference reduced the size and number of pores, porosity of the weld decreased with higher phase shifts. Stirring induced by the double pulse promoted floating and precipitation of pores. The experimental results show that a 180° phase shift leads to the most stable welding process resulting in a sound weld and an obvious fish-scale appearance. No undercut, hump, or spatter defects were observed. In addition, the deepest penetration with a uniform and smooth penetration fluctuation curve and the lowest porosity were also achieved with a phase shift of 180°.